2011
DOI: 10.1371/journal.pone.0020315
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Axons and Specific Populations of Surrounding Cells Is Indispensable for Collateral Formation in the Mammillary System

Abstract: BackgroundAn essential phenomenon during brain development is the extension of long collateral branches by axons. How the local cellular environment contributes to the initial sprouting of these branches in specific points of an axonal shaft remains unclear.Methodology/Principal FindingsThe principal mammillary tract (pm) is a landmark axonal bundle connecting ventral diencephalon to brainstem (through the mammillotegmental tract, mtg). Late in development, the axons of the principal mammillary tract sprout co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…In mouse mutants for the winged helix-loop-helix protein FOXB1 the MB does not develop properly, suggesting a crucial role for this transcription factor (Alvarez-Bolado et al, 2000;Labosky et al, 1997;Wehr et al, 1997). More recent studies revealed additional transcription factors, including SIM1, PAX6 and PITX2, that are involved in late aspects of MB differentiation, such as the development of the mammillothalamic tract (Marion et al, 2005;Skidmore et al, 2012;Szabó et al, 2011). However, only these few regulators of MA neuron development are currently known.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse mutants for the winged helix-loop-helix protein FOXB1 the MB does not develop properly, suggesting a crucial role for this transcription factor (Alvarez-Bolado et al, 2000;Labosky et al, 1997;Wehr et al, 1997). More recent studies revealed additional transcription factors, including SIM1, PAX6 and PITX2, that are involved in late aspects of MB differentiation, such as the development of the mammillothalamic tract (Marion et al, 2005;Skidmore et al, 2012;Szabó et al, 2011). However, only these few regulators of MA neuron development are currently known.…”
Section: Introductionmentioning
confidence: 99%
“…The principal mammillary tract (pmt) first appears at E10.0 and is one the earliest visible neuronal projections in the developing mouse brain (Easter et al ,1993). The pmt gives rise to mammillotegmental (mtg) and mammillotectal (mtc) tracts which are visible by E14.0 (Szabo et al ,2011). Between E17 and E18 in mouse, collaterals of the pmt branch off and project rostrally toward the anterior thalamus, giving rise to the mammillothalamic tracts (mtt) (Valverde,1998; Valverde et al .,2000).…”
mentioning
confidence: 99%
“…Analysis of mouse mutants has revealed a small number of transcription factors that regulate formation of principal mammillary, mammillothalamic, and mtg projections: FOXB1 (Alvarez‐Bolado et al ,2000), PAX6 (Szabo et al ,2011; Valverde et al ,2000), and SIM1/SIM2 (Marion et al ,2005). Collaterals from the mtg projections form in the mouse around E17.5 and give rise to the mtt, through a process that depends on PAX6 and FOXB1‐mediated signaling events at the border between dorsal and ventral thalamus (Alvarez‐Bolado et al ,2000; Szabo et al ,2011; Valverde et al ,2000). Pax6 and Foxb1 mutants both have abnormalities in the mtt but have intact mtg projections, whereas Sim1/Sim2 double mutants lack both the mtt and mtg tracts (Alvarez‐Bolado et al ,2000; Marion et al ,2005; Valverde et al ,2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, this is another version of the random versus specificity debate, as more usually formulated in the context of postsynaptic targets. In one model system, the mammillothalamic tract, branching at a specific point, is elicited by an interaction with a group of PAX6‐expressing cells, and the cooperation of transcription factors Foxb1 and Pax6 differentially regulates navigation and fasciculation (Szabo et al, ). This applies, however, to a well‐defined axon bundle, and it seems unlikely that similar mechanisms operate in the case of cortical axons, where the trajectories are typically more widely dispersed.…”
Section: Discussionmentioning
confidence: 99%